Paleoecological insights from fossil freshwater mollusks of the Kanapoi Formation (Omo-Turkana Basin, Kenya). Issue 140 (March 2020) - Van Bocxlaer, Bert
Abstract: The Early Pliocene Kanapoi Formation of the Omo-Turkana Basin consists of two fluvial/deltaic sedimentary sequences with an intermediate lacustrine sequence that was deposited in Paleolake Lonyumun, the earliest large lake in the basin. Overall, the geology and vertebrate paleontology of the Kanapoi Formation are well studied, but its freshwater mollusks, despite being a major component of the benthic ecosystem, have not been subjected to in-depth study. Here I present the first treatment of these mollusks, which have been retrieved mainly from the lacustrine but also from the upper fluvial sediments, with a focus on paleoecological implications. Overall, the freshwater mollusk fauna is reasonably diverse and contains the gastropods Bellamya (Viviparidae), Melanoides (Thiaridae), Cleopatra (Paludomidae) and Gabbiella (Bithyniidae), as well as the unionoid bivalves Coelatura, Pseudobovaria (Unionidae), Aspatharia, Iridina (Iridinidae) and Etheria (Etheriidae). Material is typically recrystallized and lithified and its taphonomy suggests deposition in a system with intermediate energy, such as a beach, with post-depositional deformation and abrasion. The mollusk assemblage is indicative of perennial, fresh and well-oxygenated waters in the Kanapoi region. It suggests that Paleolake Lonyumun had largely open shores with limited vegetation and that swampy or ephemeral backwaters were rare. Overall, these findings support earlier paleoecological interpretations based on the fish assemblage of Paleolake Lonyumun at Kanapoi. Moreover, mollusk assemblages from this lake are very similar across the Omo-Turkana Basin (Nachukui, Usno, Mursi and Koobi Fora Formations) suggesting that the lacustrine paleoecological conditions found in the Kanapoi Formation existed throughout the basin.